การบำบัดแบบกระชับเพื่อลดหรือหยุดพฤติกรรมการสูบบุหรี่ในวัยผู้ใหญ่: การพยาบาลตามหลักฐานเชิงประจักษ์ - จันมูล บุบผา; โอวยอง อทิตยา พรชัยเกตุ; ยุทธไตร ประภา (Journal of Public Health Nursing, 2016)
การศึกษาครั้งนี้มีวัตถุประสงค์ เพื่อศึกษารูปแบบการบำบัดแบบกระชับในการลดหรือหยุดพฤติกรรมการสูบบุหรี่ในวัยผู้ใหญ่ที่ได้จากหลักฐานเชิงประจักษ์จากการสืบค้นพบหลักฐานจำนวนทั้งหมด 9 เรื่อง เป็น Randomized Controlled Trial จำนวน 5 เรื่อง Quasi- experimental design จำนวน 2 เรื่อง Descriptive study จำนวน 1 เรื่องและRecommendations จำนวน 1เรื่องนำมาประเมินคุณภาพตามเกณฑ์การประเมินหลักฐานเชิงประจักษ์ของโพลิทและเบค (Polit & Beck , 2006)3 ด้าน ได้แก่ การมีความสอดคล้องกับประเด็นปัญหา การมีความหมายในเชิงของศาสตร์ และแนวโน้มความเป็นไปได้ในการนำไปใช้ในการปฏิบัติ รวมทั้งการประเมินระดับความเข้มแข็งของหลักฐานเชิงประจักษ์ ตามระบบการจำแนกหลักฐาน (Melnyk & Fineout Overholt, 2005) พบว่าการบำบัดแบบกระชับช่วยลดหรือหยุดพฤติกรรมการสูบบุหรี่ในวัยผู้ใหญ่ได้โดยเฉพาะในช่วงอายุ 18 ถึง 49 ปี โดยใช้หลักการ 5A สำหรับผู้สูบบุหรี่ทุกรายทั้งที่เริ่มต้นสูบและสูบเป็นระยะเวลานาน โดยมีขั้นตอนดังนี้ขั้นที่ 1 ถามประวัติการสูบบุหรี่ (Ask) ว่าผู้รับบริการสูบบุหรี่หรือไม่ สุขภาพเป็นอย่างไร และอุปสรรคของการหยุดสูบบุหรี่ ขั้นที่ 2 แนะนำการหยุดสูบ (Advise) เน้นเรื่องความเสี่ยงของการสูบบุหรี่ที่มีต่อสุขภาพของผู้สูบและ/หรือต่อบุคคลสำคัญในชีวิตของผู้สูบขั้นที่ 3 การประเมินความพร้อมในการหยุดสูบ (Assess) โดยประเมินระยะของการเปลี่ยนแปลงพฤติกรรมการสูบ (stage of changes) และประเมินการเสพติดนิโคติน ผู้สูบบุหรี่ที่ยังไม่พร้อมจะลดหรือหยุดการสูบบุหรี่ให้ใช้หลักการ 5R ในการสร้างแรงจูงใจให้เกิดความตระหนักในการหยุดสูบ กล่าวคือช่วยให้ผู้สูบบุหรี่มองเห็นเหตุผลที่จะหยุดสูบ(Relevance) อธิบายความเสี่ยงที่เกิดจากการสูบบุหรี่ (Risks) บอกผู้สูบบุหรี่ถึงรางวัลที่จะได้รับจากการหยุดสูบบุหรี่ (Rewards) ให้คำปรึกษาในการจัดการกับอุปสรรคขัดขวางการหยุดสูบบุหรี่ (Roadblocks) และเสริมสร้างแรงจูงใจซ้ำๆ (Repetition) ให้เลิกบุหรี่ถึงแม้ผู้สูบบุหรี่จะยังไม่เกิดการเปลี่ยนแปลงพฤติกรรม ขั้นที่ 4 การช่วยเหลือให้หยุดสูบ (Assist) ให้สอดคล้องกับระยะการเปลี่ยนแปลงพฤติกรรม โดยการให้คำปรึกษาหรือให้เอกสารความรู้ ผู้สูบบุหรี่ที่มีระดับการเสพติดนิโคตินสูง และพร้อมจะหยุดสูบบุหรี่ ให้ส่งต่อแพทย์หรือเภสัชกร เพื่อรับคำแนะนำต่อไป ขั้นที่ 5 การติดตามผลการหยุดสูบบุหรี่(Arranging Follow-up) ติดตามเมื่อผู้สูบบุหรี่เข้ารับบริการในคลินิก และติดตามทางไปรษณีย์หรือทางโทรศัพท์ การบำบัดแบบกระชับในขั้นตอนที่ 1-4 ใช้เวลาในการบำบัดประมาณ 10 -15 นาที ผู้สูบบุหรี่ที่ได้รับการช่วยเหลือและติดตามผลอย่างดี จะเกิดความพยายามที่จะลดหรือหยุดพฤติกรรมการสูบบุหรี่ได้อย่างต่อเนื่อง BRIEF INTERVENTION FOR SMOKING REDUCTION OR CESSATION IN ADULTS: EVIDENCE-BASED NURSING The present study aimed at investigating an evidence-based brief intervention for smoking reduction and cessation in adults. The search for quality evidences resulted in nine studies: five randomized controlled trials, two quasi-experimental, one descriptive, and one recommendation. The selected studies were evaluated based on the utilization criteria proposed by Polit & Beck (2006) on three aspects, that is, clinical relevance, scientific merit, and implementation potential. The strength of the evidence was determined based on criteria stated by Melnyk and Fineout-Overholt (2005). The findings have shown that brief intervention is effective in reduction and cessation of smoking among adults, especially those in the age of 18 to 49. The brief intervention consists of the 5A principle, which can be used with all smoker types, both just-started and long-time users. The steps and activities are as follows: Step 1: Ask-ask history of smoking of the clients, their health status, and obstacles for cessation; Step 2: Advise-advise for stop smoking emphasizing on risks of smoking to personal health or significant others’ health; Step 3: Assess-assess readiness to quit smoking including stages of changes in smoking behaviors and levels of nicotine addiction. Smokers who are not ready or not willing to quit smoking, the 5R principle can be employed to increase their motivation and raise their awareness of smoking cessation as follows: Relevance-help smokers to aware of good reasons to quit smoking, Risks-explain risks caused by smoking, Rewards- inform smokers about rewards of smoking cessation, Roadblocks-provide advice to or manage obstacles of cessation, and Repetition-repeatedly motivate smokers to quit. Step 4: Assist-assistance is provided to smokers to suit their stages of behavior changes; further, in cases of high level of nicotine dependence, clients would be referred to a physician or a pharmacist for proper advice. Finally, step 5: Arranging follow-up-smokers are followed up for cessation by telephone call, postcard mailing, or personal follow-ups at the clinic. The first four steps of the brief intervention last 10 to 15 minutes and can lead to smoking reduction and cessation in adults. It is emphasized that smokers who receive proper assistance and follow-up will be more likely to put their effort to continuously reduce or stop smoking behaviors.